Hydrolysis of cellulose derived from steam exploded bagasse by penicillium cellulases: comparison with commercial cellulase - Singh, Rajkumar; Varma, Anjanikumar; Laxman, Ryali Seeta; Rao, Mala (Bioresource Technology, 2009)
A complete cellulase from Penicillium pinophilum was evaluated for the hydrolysis of a-cellulose derived from steam exploded sugarcane bagasse and other cellulosic substrates. alpha-Cellulose at 1% substrate concentration was completely hydrolyzed by Penicillium cellulase within 3 h wherein at 10% the hydrolysis was 100% within 24 h with an enzyme loading of 10 FPU/g. The hydrolysate yielded glucose as major end product as analyzed by HPLC. Under similar conditions, hydrolysis of Sigmacell (microcrystalline cellulose), CP-123 (pulverized cellulose powder) and ball milled Solka Floc were 42%, 56% and 52%, respectively. Further the hydrolysis performance of Penicillium sp. cellulase is compared with Trichoderma reesei cellulase (Accellerase (TM) 1000) from Genencore. The kinetics of hydrolysis with respect to enzyme and substrate concentration will be presented. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Accellerase (TM) 1000; Enzymatic hydrolysis; High beta-glucosidase; Penicillium cellulase; Sugarcane bagasse

Effect of alkali pretreatment on the structural properties and enzymatic hydrolysis of corn cob - Sahare, Padmavati; Singh, Rajkumar; Laxman, Ryali Seeta; Rao, Mala (Applied Biochemistry and Biotechnology, 2012)
An effective alkali pretreatment which affects the structural properties of cellulose (corn cob) has been studied. The pretreatment of corn cob was carried out with different combinations of alkali at varying temperatures. The most effective pretreatment of corn cob was achieved with 1 % alkali at 50 A degrees C in 4 h. The crystallinity index (CrI) and specific surface area (SSA) of untreated corn cob was 39 % and 0.52 m(2)/g wherein after alkali pretreatment CrI decreased to 15 % and SSA increased to 3.32 m(2)/g. The fungal organism was identified as Penicillium pinophilum on the basis of ITS sequence. At 5 % substrate concentration using a complete cellulase from Penicillium pinophilum the hydrolysis of untreated corn cob with 5, 10 and 20 FPU/g enzyme loadings were 11 %, 13 % and 16 %, whereas after alkali treatment the hydrolysis increased to 78 %, 90 % and 100 %, respectively. Further hydrolytic potential of commercial cellulases viz. Accellerase (TM) 1,000, Palkofeel-30 and Palkocel-40 were investigated under similar conditions.
Keywords: Corn cob; Crystallinity index; Enzymatic hydrolysis; Penicillium pinophilum; Specific surface area